FINANCIAL PERFORMANCE ANALYSIS OF PT. INDOFOOD CBP SUKSES MAKMUR TBK YEAR 2023-2024 USING ACTIVITY RATIO - Shindu Hargo Dedali (JEB17 : Jurnal Ekonomi dan Bisnis, 2026)
We conducted research to analyze the financial performance of PT. Indofood CBP Sukses Makmur Tbk. The objective was to evaluate activity ratios using two types of ratios: Total Asset Turnover Ratio and Fixed Asset Turnover Ratio for the period 2023 to 2024.Then, this financial report was analyzed using quantitative descriptive methods. The data source was taken from the financial statements of PT. Indofood CBP Sukses Makmur Tbk for the period 2023-2024. The purpose of this research is to enable the company to measure and analyze its financial performance through the analysis of these two ratios. This will enable the company to effectively manage its liabilities and ensure smooth cash flow. Thus, the company's management is expected to be able to repay debts and run its business operations effectively. Keywords: Fixed Asset Turnover Ratio, Total Asset Turnover Ratio, & Financial Performance